The Introduction of 'Safety Science' into an Undergraduate Nursing Programme at a Large University in the United Kingdom. - White, Nick; Clark, Deborah; Lewis, Robin; Robson, Wayne (International Journal of Nursing Education Scholarship, 2016)
Implementing safety science {a term adopted by the authors which incorporates both patient safety and human factors (Sherwood, G. (2011). Integrating quality and safety science in nursing education and practice. Journal of Research in Nursing, 16(3), 226-240. doi: 10.1177/1744987111400960)} into healthcare programmes is a major challenge facing healthcare educators worldwide (; ). Patient safety concerns relating to human factors have been well-documented over the years, and the root cause(s) of as many as 65-80 % of these events are linked to human error (; ). This paper will describe how safety science education was embedded into a pre-registration nursing programme at a large UK university. The authors argue that the processes described in this paper, may be successfully applied to other pre-registration healthcare programmes in addition to nursing.